(untitled) (Homoeopathy for All, 2022)
Do you know that for effective functioning of our brain, we have to have a healthy liver? The millennial will sound like, ‘what’? The answer to this question is a big Yes. Let’s see how it is so important. Liver is one of the largest internal organs in our body. It has many roles to play ranging from fighting infection, manufacturing proteins and helping in clotting of the blood to detoxifying chemicals, which can be of natural or synthetic source. However, this highly underestimated organ is often not much cared for until the symptoms of its deterioration become very evident. NAFLD (Non Alcoholic Fatty Liver Disease) is a major concern on a global level. According to NHP, India, the prevalence of NAFLD in India is 9% to 32%. That means 1 in 5 Indians are being affected by this. (According to WHO, April 2017). Liver disease is the next major lifestyle disorder after Diabetes and BP in India.